IMPLEMENTASI PROGRAM JAMINAN PEMELIHARAAN KESEHATAN GRATIS DI PUSKESMAS GROGOL KABUPATEN SUKOHARJO - Wahyu Adi Prasetyo, Bagus Suryono (GEMA, 2015)
This research aims to know implementation of free of charge health care in Puskesmas of grogol based on the rule num. 36 Year of 2009 regarding to Health andÂ  theÂ  rightsÂ  ofÂ  patientÂ  againstÂ  servicesÂ  inÂ  PuskesmasÂ  ofÂ  GrogolÂ  accordingÂ  to program of free of charge health care insurance. BasedÂ  onÂ  theÂ  resultÂ  ofÂ  theÂ  researchÂ  performedÂ  canÂ  beÂ  concludedÂ  that whollyÂ  muchÂ  ofÂ  freeÂ  ofÂ  chargeÂ  healthÂ  careÂ  insuranceÂ  patientsÂ  areÂ  satisfiedÂ  with implementationÂ  andÂ  theÂ  rightsÂ  ofÂ  patients Â againstÂ  freeÂ  ofÂ  chargeÂ  healthÂ  care services which have been performed by Puskesmas of Grogol. Although there are several patients felt that their rights have not yet fulfilled. It happened because the patient of Jamkesmas (community health insurance) itself didnât understand their rightsÂ  asÂ  patientÂ  ofÂ  freeÂ  chargeÂ  healthÂ  careÂ  insuranceÂ  inÂ  PuskesmasÂ  Grogol. But PuskesmasÂ  ofÂ  GrogolÂ  hasÂ  whollyÂ  implementedÂ  fulfillmentÂ  ofÂ  goodÂ  servicesÂ  the rightsÂ  ofÂ  patientÂ  becauseÂ  itÂ  hasÂ  beenÂ  inÂ  accordanceÂ  withÂ  governmentÂ  rule.